Multijoint Musculoarticular Stiffness Derived From a Perturbation Is Highly Variable. Issue 9 (September 2021) - Schofield, Mike; Tinwala, Farhan; Cronin, John; Hébert-Losier, Kim; Uthoff, Aaron
Abstract : Abstract: Schofield, M, Tinwala, F, Cronin, J, Hébert-Losier, K, and Uthoff, A. Multijoint musculoarticular stiffness derived from a perturbation is highly variable. J Strength Cond Res 35(9): 2498–2503, 2021—Testing musculoarticular stiffness may provide insights into multijoint elastic properties. Yet, most research has focused on quantifying stiffness, or elastic potential, at a single joint. The purpose of this study was to quantify the test-retest reliability of musculoarticular stiffness derived from the perturbation technique across the bench pull, bench press, and squat movements. Eight resistance-trained men performed bench pull, bench press, and squat repetition maximums, after which a perturbation protocol was tested over multiple days. During the 3 movements, a brief perturbation was applied to the bar. The resulting sinusoidal wave was measured by an underbench force plate and a linear position transducer attached to the bar. From the sinusoidal wave, stiffness was derived and found to be unreliable across movements and days (change in mean: −35.1 to 15.8%; coefficient of variation: 7.1–111%; intraclass correlation: −0.58 to −0.89). Squat data were removed from the analysis entirely because of the inability to consistently determine the perturbations on the force plate. Practitioners need to be aware that musculoarticular stiffness as measured using the perturbation technique on the movements performed in this study has considerable limitations in terms of reproducibility.